Novel anti-CD4 monoclonal antibodies separate human immunodeficiency virus infection and fusion of CD4+ cells from virus binding. - Healey, D; Dianda, L; Moore, J; McDougal, J; Moore, M; Estess, P; Buck, D; Kwong, P; Beverley, P; Sattentau, Q (1990)
Human immunodeficiency virus (HIV) binds to cells via an interaction between CD4 and the virus envelope glycoprotein, gp120. Previous studies have localized the high affinity binding site for gp120 to the first domain of CD4, and monoclonal antibodies (mAbs) reactive with this region compete with gp120 binding and thereby block virus infectivity and syncytium formation. Despite a detailed understanding of the binding of gp120 to CD4, little is known of subsequent events leading to membrane fusion and virus entry. We describe two new mAbs reactive with the third domain of CD4 that inhibit steps subsequent to virus binding critical for HIV infectivity and cell fusion. Binding of recombinant gp120 or virus to CD4 is not inhibited by these antibodies, whereas infection and syncytium formation by a number of HIV isolates are blocked. These findings demonstrate that in addition to virus binding, CD4 may have an active role in membrane fusion.